The analysis of sustainability index of the people’s salt industry in Pamekasan using multi dimension scaling - Raden Faridz; Holilah Holilah; Millatul Ulya (President University, 2022)
This study aims to find out the dominant factors or the cause of failure in the salt industry and also to find out the value of the sustainability index of the people’s salt industry in Pamekasan. The analytical method used in this study is the analysis of sustainability status with the “sustainability index of salt” approach that resulted from Rapfish analysis to determine the sustainability status of the people's salt industry in Pamekasan. Based on the analysis result of the sustainability status with the sustainability index approach, it shows that the value of ecological dimension (66.09) in the category is quite sustainable, meanwhile the economic dimension (49,33), social dimension (47,06), technological dimension (43,41), and institutional and policy dimension (39,73). Each of the dimensions is classified as a less sustainable category. To improve the sustainability status of the people’s salt industry in Pamekasan, the improvements to the institutional and policy dimension must be the main priority in the management of people’s salt industry in Pamekasan. The priority of improvement is also determined by the value of leverage analysis. The highest value of the attribute on leverage analysis becomes the first attribute that must be improved, so the priority of improvement needs to be focused on people’s dependence on salt dike business, the role of farmers for business sustainability, and society’s empowerment.